PERFORMANCE OF INSPECTORATE IN SUPERVISION OF GOVERNMENT ADMINISTRATION IN BURU SELATAN REGENCY - Hendry Selanno; Marno Wance (Universitas Padjadjaran, 2021)
This article investigated Performance of the Inspectorate in Supervision of Government Administration in Buru Selatan Regency. The type of study used was descriptive research. This would provide a factual depiction regarding the application of Inspectorate function of Buru Selatan Regency. This study aimed to analyze the performance of the Inspectorate in Supervision of Government Administration in Buru Selatan Regency. This study suggested that the application of supervision either perceived from the inspection, examination to investigation, in fact it had not been effectively worked due to the fact that inaccuracy in supervising and inaccurate aberration data were discovered for apparatus inspector in the office of Inspectorate. The factors affecting the performance of inspection function for government administration in Buru Selatan regency included the skilled apparatus officers having knowledge in the field of work of which they should tackle and facilities and infrastructure assisting the performance of inspection performed by the Inspectorate Office in Buru Selatan regency. The result suggested that the knowledge in the field of work was still low. It was suggested to implement the inspection planning functions for the purpose of supporting the speed in collecting data and accurate data/information presentation to date will support the reporting of any aberration arising in regional government administration, engage the officers in Human Resources development and the fulfillment of supporting facilitates and infrastructure.